ChequeGuard: A Mobile-Enabled Blockchain Framework to Mitigate Fake Cheque Scams - Vsudevan, Asokan; Thayanithi, Manonmani; Pandiyarajan, Abinaya; N., Raja; Kumar, Arya (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Fake cheque scams remain a pressing financial concern, leading to substantial monetary losses and legal challenges. The absence of real-time authentication mechanisms often results in delayed scam detection by financial institutions. This report presents a mobilebased blockchain system using wireless communication and distributed ledger technology to authenticate cheques in real-time and prevent fraud. Our system integrates Namecoin, SHA-256 hashing, and elliptic curve digital signature algorithm (ECDSA) into a secure mobile computing environment to enable accessibility and scalability. The system has two significant operational phases: cheque issue and authentication. When issued, banks retain cheque information on the blockchain using Lagrange polynomials, and aggregation is achieved rapidly. Authentication at the point of withdrawal confirms the cheque as valid by verifying blockchain-stored data, preventing reuse and forgery. This framework helps achieve financial inclusion through the enabling of ubiquitous mobile access to secure cheque authentication services, resulting in cost-effective, real-world applications. By virtue of applying mobile technology infrastructures and safe wireless networks, the solution not only enhances transaction safety but also adheres to the changing trends in adaptive digital finance and industrial applications. Mobile apps facilitate users to scan and verify and get instant fraud alerts, highly promoting accessibility, especially for rural dwellers.